SYNTHESIS, CHARACTERIZATION, IN SILICO OPTIMIZATION, AND CONFORMATIONAL STUDIES OF METHYL 4-O-PIVALOYL-αL-RHAMNOPYRANOSIDES - Mohammed Mahbubul, Matin; Mohammad, Ibrahim; Tasnim Rahman, Anisa; Md. Rezaur, Rahman (Faculty of Science, University of Malaya, 2022)
Considering promising biological activities of natural and synthetic rhamnopyranoside esters, we have synthesized several methyl 4-O-pivaloyl-α-Lrhamnopyranosides via selective 2,3-O-acetonide protection of methyl α-Lrhamnopyranoside (4) followed by C-4 pivaloylation, and deprotection. The synthesized 4-O-pivaloate 7 and its 2,3-di-O-esters 8a-e are characterized by spectroscopy and are optimized by using density functional theory (DFT). The free energy and bond angles thus calculated are used to establish the probable conformation(s). The 2,3-O-acetonide protected rhamnopyranosides 5-6 are found to be slightly distorted from the regular 1C4 conformation, and exist between the chair and twist-boat (skew) conformation while other pivaloyl esters 7-8a-e exist in regular 1C4 chair conformation.